2010
DOI: 10.1002/hec.1528
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of opportunities in health in France: a first pass

Abstract: This article analyses the role played by childhood circumstances, especially social and family background in explaining health status among older adults. We explore the hypothesis of an intergenerational transmission of health inequalities using the French part of SHARE. As the impact of both social background and parents' health on health status in adulthood represents circumstances independent of individual responsibility, this study allows us testing the existence in France of inequalities of opportunity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 44 publications
5
131
0
7
Order By: Relevance
“…Europe as a whole reports a Gini coefficient of 0.10. Trannoy et al (2010) confirm the presence of inequality of opportunities in health in France, with a Gini coefficient of 0.155. In addition, they find that parental socioeconomic status is the most important circumstance to explain health inequalities on descendants' health through adulthood.…”
Section: A the Theory Of Equality Of Opportunitysupporting
confidence: 52%
See 1 more Smart Citation
“…Europe as a whole reports a Gini coefficient of 0.10. Trannoy et al (2010) confirm the presence of inequality of opportunities in health in France, with a Gini coefficient of 0.155. In addition, they find that parental socioeconomic status is the most important circumstance to explain health inequalities on descendants' health through adulthood.…”
Section: A the Theory Of Equality Of Opportunitysupporting
confidence: 52%
“…The theory of equality of opportunity has been applied also to health issues. For example, see Fleurbaey and Schokkaert (2009, Rosa Dias (2009), Rosa Dias andJones (2007), Trannoy et al (2010) and Jusot, Mage and Menendez (2014). Jusot et al (2010) find Gini coefficients for inequalities of opportunities in health ranging from 0.09 to 0.16.…”
Section: A the Theory Of Equality Of Opportunitymentioning
confidence: 99%
“…While variations in exogenous measures of education do not appear to explain health behaviours in a number of European settings (Reinhold and Jürges 2009, Braakman 2 The study ties in with a larger literature on the role of equality in opportunity in health care (e.g. Rosa Dias 2009;Trannoy et al 2010;Balia and Jones 2011;Jusot et al 2013;Garcia-Gomez et al 2014;Jones et al 2014). 3 Glied and Lleras-Muney (2008), for instance, found that the educated tend to benefit disproportionately from mortality-reducing medical innovations.…”
Section: Health Behaviour Along the Prolonged Life Coursementioning
confidence: 77%
“…These estimated correlations corroborate fully the relevance of the partial-circumstance problem put forward in Fleurbaey (2008), highlighting the vital importance of dealing with unobserved heterogeneity in the context of inequality of opportunity. Previous work, such as Trannoy et al (2009) and Rosa Dias (2009), do not take this into account.…”
Section: Resultsmentioning
confidence: 99%
“…Recent empirical papers, such as Trannoy et al (2009) and Rosa Dias (2009), provide evidence of substantial and persistent inequality of opportunity in health in European countries. They also suggest that unjust circumstances affect health through a network of indirect effects whose causal nexus is often ambiguous.…”
Section: Introductionmentioning
confidence: 99%